Do hypoxia/normoxia culturing conditions change the neuroregulatory profile of Wharton Jelly mesenchymal stem cell secretome? - Teixeira, Fábio G (2015)
Introduction: The use of human umbilical cord Wharton Jelly-derived mesenchymal stem cells (hWJ-MSCs) has been considered a new potential source for future safe applications in regenerative medicine. Indeed, the application of hWJ-MSCs into different animal models of disease, including those from the central nervous system, has shown remarkable therapeutic benefits mostly associated with their secretome. Conventionally, hWJ-MSCs are cultured and characterized under normoxic conditions (21 % oxygen tension), although the oxygen levels within tissues are typically much lower (hypoxic) than these standard culture conditions. Therefore, oxygen tension represents an important environmental factor that may affect the performance of mesenchymal stem cells in vivo. However, the impact of hypoxic conditions on distinct mesenchymal stem cell characteristics, such as the secretome, still remains unclear. Methods: In the present study, we have examined the effects of normoxic (21 % O2) and hypoxic (5 % O2) conditions on the hWJ-MSC secretome. Subsequently, we address the impact of the distinct secretome in the neuronal cell survival and differentiation of human neural progenitor cells. Results: The present data indicate that the hWJ-MSC secretome collected from normoxic and hypoxic conditions displayed similar effects in supporting neuronal differentiation of human neural progenitor cells in vitro. However, proteomic analysis revealed that the use of hypoxic preconditioning led to the upregulation of several proteins within the hWJ-MSC secretome. Conclusions: Our results suggest that the optimization of parameters such as hypoxia may lead to the development of strategies that enhance the therapeutic effects of the secretome for future regenerative medicine studies and applications.